2006
DOI: 10.1128/mcb.00307-06
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Physical Interaction of Yeast Mgs1 with PCNA: Impact on RAD6-Dependent DNA Damage Tolerance

Abstract: Proliferating cell nuclear antigen (PCNA), a sliding clamp required for processive DNA synthesis, provides attachment sites for various other proteins that function in DNA replication, DNA repair, cell cycle progression and chromatin assembly. It has been shown that differential posttranslational modifications of PCNA by ubiquitin or SUMO play a pivotal role in controlling the choice of pathway for rescuing stalled replication forks. Here, we explored the roles of Mgs1 and PCNA in replication fork rescue. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 29 publications
7
72
0
2
Order By: Relevance
“…1C), further indicating that the recombinant protein can recapitulate the behavior of endogenous Wrnip1. In the same fractionation experiment, Wrnip1 and Wrnip1-EGFP were also found to co-fractionate with PCNA and polymerase , both of which have been previously shown to be in complex with Wrnip1 (9,30).…”
Section: Wrnip1 Is Concentrated In Replication Factories and Othersupporting
confidence: 53%
See 1 more Smart Citation
“…1C), further indicating that the recombinant protein can recapitulate the behavior of endogenous Wrnip1. In the same fractionation experiment, Wrnip1 and Wrnip1-EGFP were also found to co-fractionate with PCNA and polymerase , both of which have been previously shown to be in complex with Wrnip1 (9,30).…”
Section: Wrnip1 Is Concentrated In Replication Factories and Othersupporting
confidence: 53%
“…In S. cerevisiae, mgs1 was found to be synthetically lethal with the rad6 and rad18 genes involved in DNA damage tolerance, indicating that Mgs1/Wrnip1 might deal with stalled replication forks (8). A further study demonstrated that yeast Mgs1 can physically interact with the DNA loading clamp PCNA 4 and suggested that Mgs1 may participate in a DNA damage tolerance pathway alternative to the Rad6-Rad18 one (9). The inferred role of Mgs1/Wrnip1 in replication has been strengthened by the evidence that Mgs1 in vitro stimulates the activity of Fen1, an endonuclease indispensable for the removal of Okazaki fragments during lagging-strand replication (10).…”
mentioning
confidence: 99%
“…The authors suggested an alternative model in which PCNA monoubiquitination may disrupt its interactions with a protein(s) that inhibits binding to the TLS polymerases. To date no such candidate protein has been identified, although we notice a recent report [130] that Mgs1, a protein with homology to E. coli RuvB and eukaryotic clamp loader protein RFC, as well as DNA-dependent ATPase activity and DNA-annealing activities [131,132], associates with PCNA and appears to repress the RAD6 pathway in the absence of exogenous damage. Other concerns with the above paradigm include the stability of monoubiquitinated PCNA, particularly in mammalian cells, that extends past the expected time required to bypass the damage [122], which would allow persistent TLS with unnecessarily increased mutation rates.…”
Section: Regulated Access Of Y-family Polymerases To the Damage Sitementioning
confidence: 96%
“…Given the ability of the UBZ domain to bind multiple types of polyubiquitin chains, as shown in this study, the specificity is more likely conferred by the substrate protein rather than a unique polyubiquitin chain assembly. PCNA is an interesting candidate for the ubiquitinated scaffold on which UBZ domain-containing proteins assemble, since Pol, Pol, RAD18, and WRNIP1/ MGS1 all bind PCNA (11,23,54,55).…”
Section: Peptidementioning
confidence: 99%
“…Yeasts that overexpress Mgs1p are generally healthy but exhibit marked sensitivity to the DNA-damaging agents hydroxyurea, methyl methanesulfonate, and UV radiation (22,23). This increase in DNA damage sensitivity upon Mgs1p overexpression is dependent on the presence of RAD18, indicating that an overabundance of Mgs1p cripples the postreplication repair pathway (23).…”
mentioning
confidence: 99%